Use of Two Stay Two Stray Model to Improve Student Learning Achievement in Batu City MAN - Lutfiana, Rose Fitria; Widodo, Rohmad; Latifah, Latifah (Universitas Nusantara PGRI Kediri, 2019)
This study aims to implement the Two Stay Two Stray (TSTS) learning model in order to improve student achievement in class XI IPA 2 Batu Aliyah Madrasah in the odd semester of the academic year 2018/2019. The research used is class action research (classroom action research) using the John Elliot model in which each cycle consists of planning, implementation, observation, and reflection. The subjects in this study were students of class XI IPA 2 in the odd semester of 2018/2019 academic year totaling 32. The variables investigated in this study were input variables (students of class XI IPA 2), process variables (Two Stay Two Stray models) and output variables (increased learning achievement). Data collection techniques used in the form of observation, interviews, study documentation and tests. The instruments used are observation assessment rubrics, interview guidelines, documentation study guides, and test questions. While the data analysis techniques used in the form of qualitative and quantitative analysis techniques. The results obtained in this study are the application of the Two Stay Two Stray model can improve the learning achievement of students of XI IPA 2 Human Rights material in the odd semester of the school year 2018/2019 with classical completeness values increased from pre-cycle by 43,1% in cycle I increased to 63.7% and the second cycle increased to 84.6%.